Environmental attitudes and awareness : a psychosocial perspective - Tankha, Geotika (Cambridge Scholars Publishing, 2017)
Environmental problems of pollution and degradation are a major source of concern globally. At all levels, efforts are being made to protect and preserve the environment from further deterioration. Measures are being taken at international, national and regional levels by governments and organisations to spread the awareness and concern for the environment and ecosystem, but these are not yet yielding the expected returns. Research has indicated that humans must be guided by values, beliefs, and individual motivating factors if attitudes are to be converted in actual behaviour. This book prese.